Novel Alloy Design Concepts Enabling Enhanced Mechanical Properties of High Entropy Alloys - Kumar, Jitesh; Jha, Saumya; Raturi, Abheepsit; Bajpai, Anurag; Sonkusare, Reshma; Gurao, N. P.; Biswas, Krishanu (Frontiers in Materials, 2022)
The emergence of high entropy alloys (HEA) in the world of materials has shifted the alloy design strategy based on a single principal element to the multi-principal elements where compositional space can cover almost the entire span of the higher dimensional phase diagrams. This approach can provide advanced materials with unique properties, including high strength with sufficient ductility and fracture toughness and excellent corrosion and wear resistance for a wide range of temperatures due to the concentrated alloying that cannot be obtained by traditional microalloying based on a single principal element. In addition, the alloy design approach provides new alloy systems in astronomical numbers with a variety of microstructural attributes that can yield different properties, and hence conventional trial and error experimental methods for alloy development are redundant. With the help of high throughput experiments along with efficient computational tools, and artificial intelligence, mechanisms-based mechanistic development of the multi-principal element alloys with tailored solid solution strengthening, stacking fault energy and microstructure is possible. The current review discusses the various design strategies based on multi-principal elements alloys in semblance with the desired mechanical properties dictated by the micro-mechanisms associated with them to overcome the bottlenecks presented by the conventional approaches with possible breakthroughs applications. The article will shed light on the current status as well as the future prospects of using these approaches to design novel HEAs.